Antioxidant and Antimicrobial Effects of Trametes versicolor (L.) Lloyd Extracts in Different Solvents - İnci, Şule; Akyüz, Mehmet; Kırbag, Sevda (My University, 2022)
Trametes versicolor (L.) Lloyd known as turkey tail, is a medicinal mushroom belonging to the Polyporaceae. Although the consumption and commercial sale of this mushroom in our country is new, it has been used for centuries as a medicine in some countries, especially in China. In this study, it was aimed to determine the antimicrobial and antioxidant effects of ethanol and methanol extracts of T. versicolor. Its antimicrobial effects were determined by disk diffusion and microdilution method using pathogenic microorganisms such as Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Bacillus megaterium, Staphylococcus aureus, Candida albicans and Trichophyton sp. Total antioxidant level, total oxidant level and DPPH radical scavenging capacity were detected for the antioxidant activity of the mushroom. According to the results obtained, it was seen that these extracts inhibit the growth of microorganisms at different rates (10-21 mm) according to the disk diffusion method. The minimal inhibitory concentrations of T. versicolor against microorganisms used were determined to be between 62.5-250 ?g/mL. The TAS and TOS values of the methanol extract were 0.72 mmol Trolox Equiv./L and 18.39, respectively, the TAS and TOS values of the ethanol extract were detected 0.88 mmol Trolox Equiv./L and 16.71 ?mol H2O2 Equiv./L, respectively.
Keywords: Trametes versicolor; Antioxidant; Antimicrobial; Medicinal mushrooms